IMPLEMENTASI PEMILIHAN MOTOR BEKAS MENGGUNAKAN METODE AHP-TOPSIS - Alviani Setya Yuniantika; Wiwien Hadikurniawati (Teknik Informatika, 2021)
A motorbike is a type of transportation that runs on an engine and has two wheels. Used is something that has been called not new. Human need for transportation means the most in the use of motorbikes. Economic limitations of some people choose to buy used motorbikes. In the selection, it is difficult to help consumers determine the choice of vehicle to be purchased. This is because there are so many types of motorbikes in one brand. This study aims to recommend a reference solution as a basis for consideration in selecting a used motorbike. This decision support system in solving this problem uses AHP and TOPSIS. The AHP method was chosen because it produces weighted criteria. Meanwhile, TOPSIS was chosen because for ranking determination, it is expected to provide the best used motorbike recommendation solutions to buyers